AKUNTABILITAS PENGELOLAAN KEUANGAN DESA DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK - Rizky Abrellian, Jevando; Handayani, Nur (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2025)
This research was conducted at Desa Kletek, located at Jalan Panglima Sudirman No. 01, Menyanggong, Kletek, Kecamatan Taman, Sidoarjo, East Java. It aimed to determine the effect of management accountability of village finances in increasing the public service quality at Desa Kletek. Good finance management accountability was expected to improve public service quality and be suited to public needs. The management accountability of village finances could be measured by using some principles: namely (1) Planning, (2) Implementing, (3) Managing, (4) Reporting, and (5) Accountability. Moreover, the research was descriptive- qualitative. The instruments in the data collection technique were interviews, documentation, and observations used to gain information. The result showed that management accountability of village finances at Desa Kletek which included planning, implementing, managing, reporting, and accountability had suited Permendagri No. 20, 2018, and fulfilled public needs. Furthermore, Desa Kletek needed to focus on some strategies to improve management accountability of village finance. They were improving transparency, empowering village apparatus capacity, utilizing local resources, encouraging public participation, and preventing corruption.